2023
DOI: 10.1002/ece2.16
|View full text |Cite
|
Sign up to set email alerts
|

2D semiconductor nanosheets for solar photocatalysis

Meng Cai,
Yixin Wei,
Yukun Li
et al.

Abstract: In the advancing world of graphene, highly anisotropic 2D semiconductor nanosheets, notable for their nanometer‐scale thickness, have emerged as a leading innovation, displaying immense potential in the exploration of renewable and clean energy production. These have garnered significant attention from researchers. The nanosheets are marked by their extraordinary electronic, optical, and chemical attributes, positioning them as attractive foundational components for heterogeneous photocatalysts. This review di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(3 citation statements)
references
References 264 publications
0
3
0
Order By: Relevance
“…9,10 The deficiencies of CdS can be overcome by morphological control, homo-/hetero-junction design, vacancy engineering, cocatalyst decoration, etc . 11…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The deficiencies of CdS can be overcome by morphological control, homo-/hetero-junction design, vacancy engineering, cocatalyst decoration, etc . 11…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that selenium’s weaker electronegativity than oxygens would increase the hydroxyl ions’ preferred attachment to catalytically active metal sites, hence promoting the latter stages of the oxygen evolution reaction (OER) process. The formation of the heterojunction in photocatalyst applications is well-known in photocatalytic water splitting, but the formation of interfacial heterojunction and the synergistic effect in electrochemical applications is still a less explored field in hydrogen evolution reaction (HER) and OER processes. Creating heterojunctions of LDHs and RuSe 2 helps in the interfacial synergistic effect between them; heterostructures act as efficient electrocatalysts for electrochemical water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…Photoelectrochemical (PEC) water splitting, which directly converts solar energy into chemical fuels, has garnered significant attention as a renewable and promising approach for green energy development. Remarkable progress has been made in enhancing the efficiency and stability of the employed photoelectrodes. , However, it is worth noting that the reaction rates for hydrogen evolution in acidic media are 2–3 orders of magnitude higher than those under alkaline conditions . Consequently, there is a pressing need for photoanodes that can activate the sluggish oxygen evolution reaction (OER) and match the photocathodes in acidic conditions, although such materials are rarely reported .…”
mentioning
confidence: 99%